On Micro Pre Operators in Micro Topological Spaces (European Journal of Pure and Applied Mathematics, 2024)
The basic objective of this research work is to introduce and investigate the properties of micro pre-frontier, micro pre-exterior, micro pre-border, micro pre-kernel using the concept of frontier, exterior, border and kernel.
Keywords: micro pre-frontier; micro pre-exterior; micro pre-border; micro pre-kernel